Aktualisasi Nilai-nilai Budaya Masjid Pathok Negoro - Indal Abror (ESENSIA: Jurnal Ilmu-Ilmu Ushuluddin, 2016)
Pathok Negoro Mosque is the cultural and religious heritage that is very monumental for Yogyakarta. As heir to the triumph of Islamic Mataram, Yogyakarta is the region with strong religiosity as well as holders of strong Javanese tradition until today. However, it must be recognized also that the current generation is getting deprived of the intellectual heritage of culture and religiosity past so it may fail to understand the meaning of the symbols attached to the mosque pathok Negoro. For that reason, this study is trying to unravel the meaning or the values of the mosque pathok Negoro formulated in two areas of study, the historicity of the mosque pathok Negoro and material symbols that exist in the mosque. Ultimately, this study offers a second interpretation of the heritage value of the order to be understood more easily to the context of the current era.[Masjid Pathok Negoro adalah peninggalan budaya dan agama yang sangat monumental bagi Yogyakarta. Sebagai pewaris kejayaan Mataram Islam Yogyakarta menjadi wilayah dengan relijiusitas yang kental serta pemegang tradisi jawa yang kuat hingga saat ini. Namun demikian harus diakui pula bahwa generasi terkini semakin terjauhkan dari warisan-warisan intelektual budaya dan relijiusitas masa lalu sehingga sangat mungkin gagal memahami makna simbol yang melekat pada masjid pathok negoro. Dengan alasan itu, kajian ini mencoba mengurai makna atau nilai-nilai dari masjid pathok negoro yang dirumuskan dalam dua wilayah kajian, historisitas masjid pathok negoro dan simbol-simbol material yang ada pada masjid tersebut. Pada akhirnya, kajian ini menawarkan interpretasi terhadap kedua warisan nilai tersebut agar dapat dipahami lebih mudah untuk konteks zaman saat ini.]